The Classic: Epiphyseal Coxa Vara or Displacement of the Capital Epiphysis of the Femur in Adolescence - Key, John Albert (Springer-Verlag, 2013)
This Classic Article is a redacted reprint of the original work by J.A. Key, “Epiphyseal coxa vara or displacement of the capital epiphysis of the femur in adolescence.” (Note the case reports and associated figures were deleted but are available in the supplemental reprint of the original article available online.) An accompanying biographical sketch of J.A. Key is available at DOI 10.1007/s11999-013-2907-9. The classic article is reprinted courtesy of The Journal of Bone and Joint Surgery from Key JA. J Bone Joint Surg. 1926;8:53–117. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11999-013-2913-y) contains supplementary material, which is available to authorized users.